2018
DOI: 10.1016/j.neubiorev.2018.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Impulsive aggression and response inhibition in attention-deficit/hyperactivity disorder and disruptive behavioral disorders: Findings from a systematic review

Abstract: Control network deficits were evidenced across clinical phenotypes in IA and RI. Dysfunctions at any level within these cortico-subcortical projections lead to deficient cognitive-affective control by ascribing emotional salience to otherwise irrelevant stimuli. The clinical implications of these findings are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
40
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 219 publications
5
40
0
3
Order By: Relevance
“…Diminished SN rsFC with left hemispheric clusters extending from the OFC to the frontal pole in cases compared to controls were only demonstrated when considering ADHD scores. In line with previous rs-fMRI studies (Broulidakis et al, 2016;Pu et al, 2017), cases exhibited an ADHD scores-related increase in rsFC and further corroborates the recent finding of overlapping deficit functioning in ADHD and disruptive behavior disorders (Puiu et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Diminished SN rsFC with left hemispheric clusters extending from the OFC to the frontal pole in cases compared to controls were only demonstrated when considering ADHD scores. In line with previous rs-fMRI studies (Broulidakis et al, 2016;Pu et al, 2017), cases exhibited an ADHD scores-related increase in rsFC and further corroborates the recent finding of overlapping deficit functioning in ADHD and disruptive behavior disorders (Puiu et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Oppositional defiant disorder (ODD) and conduct disorder (CD) are among the most common psychiatric disorders in childhood and adolescence (Polanczyk, Salum, Sugaya, Caye, & Rohde, 2015), characterized by angry and vindictive behaviors, and violating rules, norms, and rights, respectively (American Psychiatric Association, 2013). Comorbid attention-deficit/hyperactivity disorder (ADHD) symptoms are frequently present (Waschbusch, 2002) with overlapping neural deficits in prefrontal and limbic areas (Puiu et al, 2018). Recent studies of resting state fMRI (rs-fMRI) in adolescents with CD have mainly reported reduced resting state functional connectivity (rsFC) or activity.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the significant decrease in the left PHG of GMV was consistent with previous neuroimaging findings in adults and children with autism (Page et al, 2009;Kosaka et al, 2010;Mueller et al, 2013;Yu et al, 2019), Moreover, severely restricted and repetitive behaviors were associated with the PHG (Monk et al, 2009;Weng et al, 2010;Hau et al, 2019). These two brain regions are implicated in unconscious relational memory encoding, autobiographical memory (Tanweer et al, 2010;Duss et al, 2014), and socioemotional behaviors (Dawson, 1991;Yang et al, 2016;Puiu et al, 2018) that are abnormal in individuals with autistic traits and in patients with clinical ASD, such as understanding the mental state of others, emotion processing, and language (Barrett et al, 2007;Lartseva et al, 2015;Grecucci et al, 2016). As previously reported, individuals with autistic traits could communicate with others in a normal way but are burdened with more social pressure (El Kaliouby et al, 2006).…”
Section: Discussionsupporting
confidence: 86%
“…The life domains that are mostly impaired in individuals with ADHD are the academic, occupational, social, mental-health and self-conceptual ones, negatively impacting the lives of children and of their families (Barkley et al 2008;Matheson et al 2013;Stein, 2008). ADHD is described as a self-regulation deficit (Barkley 1997;Puiu et al 2018;Shiels and Hawk Jr 2010). Core symptoms are associated with problems in maintaining goals and plans, and an insufficient ability to inhibit impulsive responses (Sharma and Couture 2014).…”
mentioning
confidence: 99%